2020
DOI: 10.1364/boe.395432
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz spectroscopic diagnosis of early blast-induced traumatic brain injury in rats

Abstract: The early diagnosis of blast-induced traumatic brain injury (bTBI) is of great clinical significance for prognostication and treatment. Here, we report a new strategy for early bTBI diagnosis through serum and cerebrospinal fluid (CSF) based on terahertz time-domain spectroscopy (THz-TDS). The spectral differences of serum and CSF for different degrees of experimental bTBI in rats have been demonstrated in the early period. In addition, the THz spectra of total protein in the hypothalamus and hippocampus were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Using THZ-TDS detection, Png et al discovered that the refractive index of brain tissue from patients with Alzheimer's disease was significantly higher than that of healthy patients (Png et al, 2009), which was linked to amyloid aggregation and fibrosis in Alzheimer's disease brain tissue samples. THz-TDS was found up to 95.5% accurate in the early diagnosis of explosive brain injuries in another study (Wang et al, 2020). The findings revealed that in the early stages of the disease, there were differences in the serum and cerebrospinal fluid of blast-induced traumatic brain injury (bTBI) rats.…”
Section: Ll Open Accessmentioning
confidence: 95%
“…Using THZ-TDS detection, Png et al discovered that the refractive index of brain tissue from patients with Alzheimer's disease was significantly higher than that of healthy patients (Png et al, 2009), which was linked to amyloid aggregation and fibrosis in Alzheimer's disease brain tissue samples. THz-TDS was found up to 95.5% accurate in the early diagnosis of explosive brain injuries in another study (Wang et al, 2020). The findings revealed that in the early stages of the disease, there were differences in the serum and cerebrospinal fluid of blast-induced traumatic brain injury (bTBI) rats.…”
Section: Ll Open Accessmentioning
confidence: 95%
“…Many pathologies are in fact due to an alteration of the aminoacetic sequences and/or functional protein alterations. Recently, Wang et al [205] exploited time-resolved THz spectroscopy to analyze serum and cerebrospinal fluid (CSF) extracted from rats at different times after blast-induced head injury (bTBI), from both the hypothalamus and the hippocampus.…”
Section: Current Status Of Thz Spectroscopy For Protein Researchmentioning
confidence: 99%
“…In recent years, numerous THz applications have been developed in biomedical and engineering fields [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. In particular, they can be used for disease diagnosis in biological samples [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], characteristic analysis of biological samples [ 21 , 22 , 23 , 24 , 25 , 26 ] and biomolecules [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ], non-destructive detection of artifacts and objects in samples [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], identification of hidden materials and their properties [ 42 , 43 , 44 , 45 ], estimation of the components in a mixture [ 46 , 47 , 48 , 49 , 50 , 51 ], and so on. Due to the rapid evolution of THz technologies and their increased availability, it is expected that the appli...…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous THz applications have been developed in biomedical and engineering fields [1][2][3][4][5][6][7]. In particular, they can be used for disease diagnosis in biological samples [8][9][10][11][12][13][14][15][16][17][18][19][20], characteristic analysis of biological samples [21][22][23][24][25][26] and biomolecules [27][28][29][30][31][32][33], non-destructive detection of artifacts and objects in samples [34][35][36][37][38][39][40][41], identification of hidden materials and their properties [42][43][44][45], estimation of the components in a mixture [46][47][48]…”
Section: Introductionmentioning
confidence: 99%